ANALISIS PENGARUH ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSET (ROA) TERHADAP MARKET VALUE ADDED (MVA) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Putri, Kiki Ariani; Tumewu, James (Liability, 2019)
This study examines the effect on performance measurement using the traditional method of Return On Assets (ROA) and the Economic Value Added (EVA) on the Market Value Added (MVA) in the manufacturing companies on the Stock Exchange Indonesi terdftar from 2010-2012 . The analysis technique used is multiple linear regression analysis using SPSS 15.0. This study uses secondary data in the form of financial statements obtained through the center of reference data available on the Indonesia Stock Exchange website , the samples used are 10 companies listed in Indonesia Stock Exchange during 2010-2012 , this study uses two independent variables (EVA and ROA) and one dependent variable (MVA). The results of this study showed that simultaneous Economic Value Added (EVA) and return on assets (ROA) showed a significant effect on Market Value Added (MVA), while partially Economic Value Added (EVA) significantly affects the Market Value Added (MVA) and return on assets (ROA) did not significantly influence the Market Value Added (MVA).